1991
DOI: 10.1111/j.1699-0463.1991.tb01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 30 μg and 120 μg gentamicin disks for the prediction of gentamicin resistance in Enterococcus faecalis

Abstract: Kronvall, G., Ringertz, S., Nystrom, S., Rylander, M. & Theodorsson, E. Comparison of 30 pg and 120 pg gentamicin disks for the prediction of gentamicin resistance in Enterococcus fueculis. APMIS Single strain regression analysis was performed on PDM I1 medium for E. fueculis with 10, 30 and 120 pg gentamicin disks using E. fueculis, strain ATCC 29212 as the reference. This method permits the calculation of zone diameters corresponding to different MIC values for different disk contents. The lack of discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…First, the exact figure from NRI calculations is rounded up, thereby including more isolates. Second, an analysis of the WT peak in an inhibition zone diameter histogram showed that the WT population was slightly peaked and skewed toward higher zone values (13). This would also apply to MIC distributions, although the precision is lower compared to disc diffusion tests.…”
Section: Discussionmentioning
confidence: 99%
“…First, the exact figure from NRI calculations is rounded up, thereby including more isolates. Second, an analysis of the WT peak in an inhibition zone diameter histogram showed that the WT population was slightly peaked and skewed toward higher zone values (13). This would also apply to MIC distributions, although the precision is lower compared to disc diffusion tests.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds rather well to the distribution of susceptible isolates, the WT population. Such a distribution was analysed regarding conformity with a normal distribution and was found to fit well, except being slightly peaked and with a kurtosis towards higher zone values [41]. In fact, a WT…”
Section: Estimation Of Wild-type Populations and Cut-off Valuesmentioning
confidence: 94%
“…SRA can be done in individual laboratories where interlaboratory variation otherwise would have resulted in erroneous interpretations. The SRA method has been applied to several combinations of antimicrobials and species [15,[37][38][39][40][41][42][43][44]. A simple explanation of SRA with a review was published in 1991 [45].…”
Section: Page 10 Of 38mentioning
confidence: 99%
See 1 more Smart Citation
“…Parametric statistical measures, such as the mean and standard deviation (S.D. ), have been shown earlier to describe zone diameter histogram populations accurately [32]. The susceptible population is thereby defined and a lower limit for susceptibility can be set to any value of the S.D.…”
Section: Nrimentioning
confidence: 99%